Factors influencing parents' decision to enrol their children at MTsN 2 Mandailing Natal school as an educational institution based on Islamic values - Ahmad Asrin; Rohman; Dedi Sahputra Napitupulu (LPPM Universitas Ibn Khaldun, Bogor, 2026)
This study aims to analyze the factors influencing parents' preferences in choosing MTsN 2 Mandailing Natal as an educational institution for their children, and how these preferences reflect the community's orientation toward religion-based education. This study used a descriptive qualitative approach with in-depth interviews with 30 parents who chose MTsN 2 as a school for their children. The sampling technique used was purposive sampling, where informants were selected based on certain criteria relevant to the research focus. Data analysis was conducted using interactive qualitative analysis techniques, through the stages of data reduction, data presentation, and conclusion drawing. The results show that parents' preferences for MTsN 2 Mandailing Natal are not only based on religious reasons, but also on academic factors, teacher role models, student discipline, and the safety of the school environment. Most parents chose MTsN 2 because of the religious values ​​taught at the madrasah, which are considered to help shape children's character and morals. In addition, parents feel that MTsN 2 is better able to maintain discipline and protect their children from negative influences often found in public schools. These findings illustrate that parental preferences are more complex and based on a more holistic combination of rational and social factors. This research contributes to the development of Islamic education theory by emphasizing the importance of balancing academic education and religious-based character development in educational institutions. The practical implication of these findings is the importance for madrasah administrators to continuously improve the quality of educational services, focusing not only on academic aspects but also on character development and strengthening religious values.